Modelling Migration and Regional Labour Markets: An Application of New Economic Geography Model Rhomolo - D'artis Kancs; Enrique Lopez-Bazo; Fabio Manca; Damiaan Persyn (European Regional Science Association (ERSA), 2012)
The objective of the present paper is to study the impact of R&D investment on inter-regional labour migration and inter-sectoral labour reallocation in the EU, specifically at regional level. In order to capture important general equilibrium effects, we employ a structural NEG model called RHOMOLO. The RHOMOLO model is a dynamic spatial general equilibrium (DSGE) modelling framework capturing 270 NUTS2 regions in EU-27, and decomposing the economy into 6 sectors. The current base year of RHOMOLO, and to which structural parameters' estimates are used to calibrate the model, is 2007. As a first step of our analysis we econometrically estimate both (i) within country and (ii) across countries migration flows as a function of relative population, relative real wages per employee, relative unemployment rate and regional connectivity (as proxied by bilateral trade between origin and destination regions normalised by the total of their GDP). Our econometric findings suggest that within-country migration is subject to much the same economic forces as between-country migration, with estimates of the coefficients of relative wages and relative unemployment within in the same range. Secondly, we econometrically estimate the R&D and human capital elasticities, which are key parameters in the semi-endogenous growth module of RHOMOLO to assess the impact of R&D investment on TFP growth. In our next step we produce regional scenarios for R&D investments according to the objective of the Europe 2020 strategy and use them to simulate a shock in R&D investments at the regional levels needed to meet the Europe 2020 strategy. Finally, we combine the previous work together in order to simulate the impact on employment levels of regional R&D investments through the geographically heterogeneous effect that they have on migration flows and on labour supply in each EU region. The geographical distribution of R&D expenditures is shown to affect migration flows as well as employment levels at the regional level by increasing skills in those regions affected by R&D expenditures. Spillover effects on neighbouring regions are also observed.
Keywords: 330